PENGARUH TRUEVIEW ADS YOUTUBE TERHADAP SIKAP KONSUMEN DAN DAMPAKNYA TERHADAP NIAT BELI PRODUK UNIQLO - Yolanda, Valent; Anggawidjaja, Agus Hasan Pura (Universitas Katolik Parahyangan, 2024)
Technological advances and the rapidly increasing internet use are currently good opportunities for companies. Social media and online platforms, including YouTube, can be used to advertise brands. YouTube offers a trueview ads feature (ads that appear or are displayed when a YouTube user watches a video). With YouTube trueview ads, companies are required to be able to create attractive advertisements so that viewers do not choose the